2022
DOI: 10.1177/17448069221107810
|View full text |Cite
|
Sign up to set email alerts
|

Effects of administration of α2 adrenergic receptor agonist into psoas major muscle on inflammatory pain induced by injection of complete Freund’s adjuvant in rats

Abstract: α2 adrenergic agonists are widely used in clinical anesthesia and ICU sedation owing to their effective sedative and analgesic effects. Lumbago and leg pain is the most common clinical pain disease. Studies have reported that lumbago and leg pain is associated with dysregulation of paravertebral muscles, especially psoas major muscles. In the present study, a unilateral lower extremity chronic inflammation and pain model was established by subcutaneous administration of low-dose complete Fredrin's adjuvant (CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In one study, preinjection of clonidine into the hind paw of rats reduced the sensitivity of the sole to thermal stimulation, 28 it may be that norepinephrine inhibits capsaicin‐induced transient receptor potential vanillin 1 (TRPV1) activity via α2 receptor in rat dorsal root ganglion (DRG) neurons. Mechanical hyperalgesia induced by Fredlin adjuvant (CFA) can be relieved by injection of α2 adrenergic receptor agonists into the psoas major muscle 29 . Therefore, it is considered that the improvement of algesthesia induced by guanfacine in this study may be achieved through the effect of peripheral adrenergic α2 receptor.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In one study, preinjection of clonidine into the hind paw of rats reduced the sensitivity of the sole to thermal stimulation, 28 it may be that norepinephrine inhibits capsaicin‐induced transient receptor potential vanillin 1 (TRPV1) activity via α2 receptor in rat dorsal root ganglion (DRG) neurons. Mechanical hyperalgesia induced by Fredlin adjuvant (CFA) can be relieved by injection of α2 adrenergic receptor agonists into the psoas major muscle 29 . Therefore, it is considered that the improvement of algesthesia induced by guanfacine in this study may be achieved through the effect of peripheral adrenergic α2 receptor.…”
Section: Discussionmentioning
confidence: 94%
“…Mechanical hyperalgesia induced by Fredlin adjuvant (CFA) can be relieved by injection of α2 adrenergic receptor agonists into the psoas major muscle. 29 Therefore, it is considered that the improvement of algesthesia induced by guanfacine in this study may be achieved through the effect of peripheral adrenergic α2 receptor. The use of guanfacine was also associated with a decrease in GFAP‐positive cells in the prefrontal lobe and cingulate gyrus, just as activation of microglial cells in the spinal cord after peripheral nerve injury may make pain persist.…”
Section: Discussionmentioning
confidence: 95%
“…Esketamine mainly exerts analgesic effects by blocking NMDA receptors and also relieves opioid-induced hyperalgesia [ 32 ]. Dexmedetomidine excites α 2 adrenergic receptors to inhibit the release of excitatory neurotransmitters and hyperpolarize cells, thereby inhibiting pain signaling [ 33 ]. Both can reduce the use of opioid analgesia through eliciting multimodal analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…It is also associated with reduced blood pressure and heart rate [ 16 ]. DEX also has vasoconstrictor features by acting on alpha-2 β receptors of peripheral blood vessels and has been shown to enhance the anesthetic effects and prolong the duration of action of LIDO ( Table 1 ) local anesthesia as well as reduce the required dosage of anesthetic drugs [ 17 ]. Therefore, it is suggested that DEX can be helpful for anxiety control in patients undergoing dental surgery when achieving adequate patient cooperation is a challenging issue for the operator [ 18 ].…”
Section: Introductionmentioning
confidence: 99%